Response of grain-filling rate and grain quality of mid-season indica rice to nitrogen application - Jing ZHANG; Yan-yan ZHANG; Ning-yuan SONG; Qiu-li CHEN; Hong-zheng SUN; Ting PENG; Song HUANG; Quan-zhi ZHAO (Journal of Integrative Agriculture, 2021)
Nitrogen is one of the important factors for high yield of rice. Apart from high yield, high quality has become the current urgent demand for rice production. Grain-filling stage is crucial for rice yield and quality formation. However, the effect of nitrogen on grain-filling characteristics and the relationship of grain-filling characteristics and rice quality of mid-season indica rice were still unclear. A field experiment was carried out to ascertain the critical grain-filling characteristics that contribute to rice milling quality, appearance quality and cooking and eating quality under nitrogen applications. The results showed that nitrogen applications prolonged the duration of superior and inferior grain filling. The mean grain-filling rate (Gmean) and the maximum grain-filling rate (Gmax) of the inferior grains were positively correlated with chalky kernel rate, chalkiness, and amylose content. The time reaching the maximum grain-filling rate (Tmax G) of the inferior grains was positively correlated with brown rice rate, milled rice rate, and head milled rice rate. Chalky kernel rate and chalkiness were negatively correlated with peak paste viscosity and breakdown viscosity. Less amylose content and more crude protein content were detected in nitrogen application of Liangyoupei 9 and Y Liangyou 2 both in 2016 and 2017. According to the correlation analysis, better cooking and eating quality of Y Liangyou 2 which had less amylose content might result from its higher Gmax and Gmean of inferior grain than that of Liangyoupei 9 in the treatments of nitrogen application. These results indicated that the prolonging grain-filling duration and increasing grain weight at the maximum grain-filling rate of inferior grains contributed to the improvement of milling quality, appearance quality, and cooking and eating quality of mid-season indica rice under appropriate nitrogen applications.